(untitled) (Research, Society and Development, 2020)
The objective of this work was to evaluate the influence of different doses of spent coffee grounds on soil microorganisms responsible for nutrient cycling and the development of corn crop under no-tillage. The trial was conducted in a field at the State Center for Agricultural Professional Education Fernando Costa, in a randomized block with 4 treatments, with increasing doses, 0, 3, 6 and 9 t ha-1 of coffee grounds. Microbial biomass carbon (CBM), baseline respiration (RBS), microbial and metabolic quotient (qMIC and qCO2), plant development (corn) and productivity were evaluated. At the dose of 9 t ha-1 of spent coffee grounds, there was an increase in organic matter and microbial biomass (219.01) and qMIC (1.5). With increased microbial activity, the development of the plant was 20% higher compared to the control, plant height (2.21) and stem diameter (2.99). Consequently, the productivity was 42 bags ha-1 higher than the control. Thus, we can conclude that spent coffee grounds can be a viable alternative for use as organic fertilizer in agriculture.